Constructing and Testing a Vacuum Frying for Salacca Fruit Using a Reused Vacuum Pump - Irwansyah; Ainun Rohanah; Edi Susanto (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2020)
Fruit chips are the result of the processing of horticultural produce that does not use high temperatures. The abundance of agricultural products in Indonesia and still not many agricultural product processing technology make the fruit frying business a good prospect. On the one hand, processing fruit chips with hight water content characteristics require a special frying technology called low temperature and pressure. On the other hand, this equipment is still not widely developed or even owned by small and medium enterprises. Therefore, this study aims to design and test a vacuum fryer for salacca. The vacuum method used is to use a vacuum pump recycled from the vacuum part of the cooling unit. The parameters observed were the effective capacity of the equipment, water content, and organoleptic test. The research results showed that the equipment's effective capacity was 0.26 kg/hr with 1.63% (w.b.) water content.